2022
DOI: 10.1097/md.0000000000030031
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic significance of sarcopenia in acute ischemic stroke

Abstract: Because sarcopenia is widely distributed in patients with acute ischemic stroke (AIS) and has not attracted enough attention, this study aims to explore the relationship between sarcopenia defined by temporal muscle thickness (TMT) and physical function and prognosis of patients with AIS. A total of 265 hospitalized nonsurgical AIS patients from 2015 to 2018, with an age range of 28 ~ 92, were analyzed retrospectively. The median value of TMT was used as the risk classification index of sarcopenia. The main re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…[12,13] However, this also means that the corresponding changes in body composition can also objectively represent the state of the body, so it is important to measure and evaluate them dynamically, among which the quantitative analysis of body components such as skeletal muscle by Advantage Workstation through large-scale equipment such as CT has been widely proved to be effective and highly reproducible among different researchers, which is the same as our research results. [14,15] More importantly, our results reflect an interesting change in predictive power when sarcopenia is combined with other prognostic factors. Based on the multifactorial results of visceral obesity with sarcopenia, the prediction ability of the combination of skeletal muscle and fat components exceeds that of any single component.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…[12,13] However, this also means that the corresponding changes in body composition can also objectively represent the state of the body, so it is important to measure and evaluate them dynamically, among which the quantitative analysis of body components such as skeletal muscle by Advantage Workstation through large-scale equipment such as CT has been widely proved to be effective and highly reproducible among different researchers, which is the same as our research results. [14,15] More importantly, our results reflect an interesting change in predictive power when sarcopenia is combined with other prognostic factors. Based on the multifactorial results of visceral obesity with sarcopenia, the prediction ability of the combination of skeletal muscle and fat components exceeds that of any single component.…”
Section: Discussionmentioning
confidence: 51%
“…[12,13] However, this also means that the corresponding changes in body composition can also objectively represent the state of the body, so it is important to measure and evaluate them dynamically, among which the quantitative analysis of body components such as skeletal muscle by Advantage Workstation through large-scale equipment such as CT has been widely proved to be effective and highly reproducible among different researchers, which is the same as our research results. [14,15]…”
Section: Discussionmentioning
confidence: 99%
“…[4] Researchers have recently focused on sarcopenia in acute ischemic stroke. [5][6][7][8] While making these evaluations of sarcopenia, researchers tended to evaluate different parameters in terms of neurological disorders. They stated that temporal muscle thickness (TMT) and area were important for sarcopenia in patients with subarachnoid hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…TMT correlates with sarcopenia risk [ 16 ] and hand grip strength [ 17 ] in patients with stroke. A low TMT has been found to be associated with significantly decreased survival [ 18 ], and severe dysphagia [ 19 ] in patients with acute stroke. Katsuki et al reported TMT cutoff values of 4.9 mm for women and 6.7 mm for men when identifying physical function at 3 months post-stroke in patients with subarachnoid hemorrhage under 75 years of age [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Katsuki et al reported TMT cutoff values of 4.9 mm for women and 6.7 mm for men when identifying physical function at 3 months post-stroke in patients with subarachnoid hemorrhage under 75 years of age [ 20 ]. TMT has also been shown to be associated with nutritional status in older adults [ 21 ] and progression-free survival in patients with head and neck squamous cell carcinoma [ 18 ]. TMT can be measured using computed tomography (CT), magnetic resonance imaging (MRI), and ultrasonography.…”
Section: Introductionmentioning
confidence: 99%